2018
DOI: 10.1159/000486021
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Acral Spared Phenomenon Related to Systemic Anticancer Therapies

Abstract: We have observed three patients on anticancer therapies presenting with asymmetric acral spared phenomenon and found six identical cases in the literature. All of them had common features, an alteration of the peripheral nerves affecting a limb unilaterally that was spared by a hand-foot syndrome or hand-foot skin reaction. A drug-induced neurotropic effect sounds logical for developing such alterations with specific chemotherapeutic agents (taxanes, cap­ecitabine), while we have not found good explanations co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Similarly, a phototoxic mechanism for photo-onycholysis has been advanced by some authors but remains to be confirmed [87]. The integrity of peripheral nerves appears to be a substantial factor for developing nail unit alterations with taxanes, suggesting a drug-induced neurotropic effect [88]. It is hypothesised that the higher incidence of onycholysis with the weekly paclitaxel regimen (1-hour infusion) may be correlated to an increased systemic exposure to the cremophor vehicle (paclitaxel solvent) [89].…”
Section: Diagnosis and Pathology/molecular Biologymentioning
confidence: 99%
“…Similarly, a phototoxic mechanism for photo-onycholysis has been advanced by some authors but remains to be confirmed [87]. The integrity of peripheral nerves appears to be a substantial factor for developing nail unit alterations with taxanes, suggesting a drug-induced neurotropic effect [88]. It is hypothesised that the higher incidence of onycholysis with the weekly paclitaxel regimen (1-hour infusion) may be correlated to an increased systemic exposure to the cremophor vehicle (paclitaxel solvent) [89].…”
Section: Diagnosis and Pathology/molecular Biologymentioning
confidence: 99%